Pemberdayaan UMKM Lokal Melalui Sosialisasi, Pelatihan SEO, dan Google Maps Di Kelurahan Tanjungsari, Surabaya - Santoso, Marsha Natania; Arianto, Dita Charolina Evangelista Cahyani; Vebryna, Esha Nanda; Valencia, Aisa Renata; Chairil, Augustin Mustika (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy but continue to face major challenges in digitalization, particularly in optimizing online promotional media. Through the Community Service Program (KKN) In Tanjungsari Village, Sukomanunggal District, Surabaya City, a team of students from Universitas Pembangunan Nasional "Veteran" Jawa Timur implemented an empowerment program entitled "Upgrading MSMEs: Understanding SEO and Google Maps to Penetrate the Digital Market." This initiative included outreach, training, and direct assistance in utilizing local Search Engine Optimizatio (SEO) and Google Maps to enhance business visibility. The results of the program showed an increase in digital understanding and skills among MSME actors, marked by a growing number of businesses successfully creating and verifying their Google Maps accounts. This program demonstrates that an educational and participatory approach is effective in driving the digital transformation of local MSMEs and enhancing their competitiveness in the digital market.